2019
DOI: 10.1002/cbic.201800641
|View full text |Cite
|
Sign up to set email alerts
|

Automated Glycan Assembly of Plant Oligosaccharides and Their Application in Cell‐Wall Biology

Abstract: The plant cell wall provides the richest available resource of fermentable carbohydrates and biobased materials. The main component of plant cell walls is cellulose, which is the most abundant biomolecule on earth. Apart from cellulose, which is constructed from relatively simple β‐1,4‐glucan chains, plant cell walls also contain structurally more complex heteropolysaccharides (hemicellulose and pectin), as well as lignin and cell‐wall proteins. A detailed understanding of the molecular structures, functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, we decided to synthesize chemically the pure MLG structures to characterize the PTI activity of additional structures further. The analysis of Ca 2+ influxes triggered by these pure, synthetic structures indicated that MLG oligosaccharides with DP3 and DP4 were not active (Figure S6a), probably due to the presence of an aminoalkyl linker at their reducing end, which is required for the synthesis process (Figure S6c; Bartetzko and Pfrengle, 2019;Dallabernardina et al, 2017) and that would affect the tri-dimensional structures of these synthetic oligosaccharides and may interfere with their perception by PRRs. However, MLG oligosaccharides of higher DP (6 and 8) were active in triggering Ca 2+ influxes (Figure S6b; MLG44343 0 , MLG44434 0 , MLG43344 0 , MLG3434443 0 ).…”
Section: Mlg Oligosaccharides Trigger Ca 2+ Influxes In Arabidopsismentioning
confidence: 99%
“…In addition, we decided to synthesize chemically the pure MLG structures to characterize the PTI activity of additional structures further. The analysis of Ca 2+ influxes triggered by these pure, synthetic structures indicated that MLG oligosaccharides with DP3 and DP4 were not active (Figure S6a), probably due to the presence of an aminoalkyl linker at their reducing end, which is required for the synthesis process (Figure S6c; Bartetzko and Pfrengle, 2019;Dallabernardina et al, 2017) and that would affect the tri-dimensional structures of these synthetic oligosaccharides and may interfere with their perception by PRRs. However, MLG oligosaccharides of higher DP (6 and 8) were active in triggering Ca 2+ influxes (Figure S6b; MLG44343 0 , MLG44434 0 , MLG43344 0 , MLG3434443 0 ).…”
Section: Mlg Oligosaccharides Trigger Ca 2+ Influxes In Arabidopsismentioning
confidence: 99%
“…We have recently developed a glycan array equipped with 88 synthetic plant oligosaccharides to determine the binding epitopes of cell wall glycan‐directed antibodies . These oligosaccharides represent fragments of natural hemicellulose, hydroxyproline‐rich glycoproteins, and pectic polysaccharides, and include arabinoxylan‐, type I and type II arabinogalactan‐, xyloglucan‐, and mixed‐linkage glucan‐ related structures . This array is being continuously expanded with newly synthesized oligosaccharides to increase the covered chemical space.…”
Section: Introductionmentioning
confidence: 88%
“…The first solution phase synthesis of a nonasaccharide repeating unit was realized using a convergent approach [ 101 ]. The process was later simplified using AGA and several XG oligosaccharides were prepared [ 102 ]. Representative examples are 19 and 20 ( Scheme 3 ) [ 103 ], as well as the galactose-containing compounds 21 and 22 [ 104 ].…”
Section: Reviewmentioning
confidence: 99%